Exploring Memorization Patterns in the Tahfidz and Tarjamah Qur’an Programs - Suryana, Ermis; Supriadi, Udin; Fikri, Miftahul; Efriani, Arvin; Langputeh, Sukree (Jurnal Pendidikan Islam, 2024)
The memorization and understanding of the Qur'an play a vital role in shaping a Qur'anic generation. This study aims to explore the memorization patterns in the Tahfidz and Tarjamah Qur'an programs at Darul Hufadz Islamic Senior High School. Using a qualitative research approach, data were gathered through in-depth interviews, participatory observation, and documentation from 38 informants, including the principal, five mentor teachers, and 32 students. Data analysis followed a process of reduction, presentation, and verification. The findings indicate that the Tahfidzul Qur'an program follows a daily memorization pattern known as "One Day One Verse," where students memorize one verse and its translation each day. The program emphasizes regular recitation, memorization, comprehension, and the practical application of the Qur'an's teachings, with parental oversight. Collaborative reading sessions between teachers and students, coupled with repetition—where verses are repeated over 40 times and listened to more than 60 times—reinforce the memorization process. This structured approach effectively cultivates a Qur'anic generation, ensuring deep engagement with the Qur'an. The study highlights the importance of consistent memorization routines and active teacher involvement in fostering both cognitive and spiritual development among students.